The Antibody Assay in Suspected Autoimmune Encephalitis From Positive Rate to Test Strategies - Deng, Qun; Liu, Ye; Mao, Zhifeng; Chen, Yun; Ping, Yue; Zhu, Guoqiang; Zhao, Weiqing; Hu, Xiao; Zhou, Hao (Frontiers in Immunology, 2022)
Objective The aim of this study was to analyze the positive rate and test strategies of suspected autoimmune encephalitis (SAE) based on an antibody assay. Methods Patients who were diagnosed with suspected autoimmune encephalitis in Guizhou Province between June 1, 2020, and June 30, 2021 and who had anti-neuronal autoantibodies detected by Guizhou KingMed Diagnostics Group Co., Ltd. were included in this study. The positive rate and the test strategies were analyzed based on the results of the anti-neuronal antibody assay. Results A total of 263 patients with SAE were included, 58.2% (153/263) of whom were males, with a median age of 33 years (1-84 years). 84% (221/263) of all patients completed both serum and CSF tests. A total of 46.0% (121/263) of SAE patients received the AE-6 examination package. The antibody-positive rate was 9.9% (26/263) in the current cohort, with an observed incidence of antibody positive of 0.2 in 100,000 (26/11,570,000, 95% CI: 0.15-0.30), and the estimated incidence was 0.9 in 100,000 (95% CI: 0.84-0.95) of the total population. A total of 9 different anti-neuronal antibodies were detected. Anti-NMDAR antibody was the most common antibody in 46.2% (12/26) of subjects, 70.0% (7/10) of whom were children, followed by anti-Caspr2 antibody in 30.8% (8/26); the remaining 7 antibodies were detected in 23.1% (6/26) of the population. There were no obvious differences among age, sex or season in the positive rate of anti-neuronal antibodies. The cost of antibody testing per capita was 439.30 (SD±195.10). The total cost of AE-14 was the highest at 48.016.81 (41.56%) among all examination packages. Conclusions This study described the positive rate associated with AE-related anti-neuronal antibodies and test strategies in the current cohort, which provides a basis for clinicians in clinical practice.